2020
DOI: 10.1021/jacs.0c00640
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Polymeric Metal–Organic Nanocapsule Networks via Supramolecular Coordination-Driven Self-Assembly

Abstract: Polymeric metal–organic nanocapsule networks (polyMONCs), where metal–organic nanocapsules (MONCs) are connected by functional polymers, could possess the properties of traditional polymers and also retain the structures of MONCs. In this work, we constructed novel polyMONCs based on Mg-seamed pyrogallol[4]­arene-containing MONCs through supramolecular coordination-driven self-assembly. The MONCs can be successfully polymerized using poly­(ethylene glycol) as the linker, and the prepared polyMONCs can be furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 48 publications
0
49
0
Order By: Relevance
“…The incorporation of MOCs into thin films has been reported, including examples where MOCs are crosslinked to form MOFs. [152] Other studies have demonstrated the incorporation of MOCs into polymer films and gels [153] or the immobilisation of MOCs onto alumina substrates. [154] In the latter study it was demonstrated that the MOCs retained their ability to trap and release guest molecules even when tethered to the material.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of MOCs into thin films has been reported, including examples where MOCs are crosslinked to form MOFs. [152] Other studies have demonstrated the incorporation of MOCs into polymer films and gels [153] or the immobilisation of MOCs onto alumina substrates. [154] In the latter study it was demonstrated that the MOCs retained their ability to trap and release guest molecules even when tethered to the material.…”
Section: Discussionmentioning
confidence: 99%
“…These kinds of materials can possess porosity without the need for long-rage order, and improved mechanical properties over MOFs. ( Lal et al, 2019b ; Zhao et al, 2020 ; Carné-Sánchez et al, ; Schneider et al, 2020 ; Lal et al, 2019a ; Shao et al, 2020 ). Advances in this area have been made possible by fundamental studies into the compatibility of M 2 paddlewheel-based MOCs with various surface functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic cages (MOCs) with specic congurations and functions have emerged as an appealing topic in recent coordination chemistry. [47][48][49] MOCs with unique geometries and large inner voids can be employed as building blocks to construct CPMs with a hierarchical pore structure through a variety of coordination and supramolecular interactions, which provide potential applications in the elds of adsorption/ separation, heterogeneous catalysis, drug release, and mimicry of biological processes. 3,16,[35][36][37] In particular, tetrahedral MOCs (M 4 L 6 or M 4 L 4 -type) as typical polyhedral structures, are ideal secondary building units (SBUs) to further construct CPMs.…”
Section: Introductionmentioning
confidence: 99%